2007
DOI: 10.1080/01677060701503140
|View full text |Cite
|
Sign up to set email alerts
|

A GENETIC MODIFIER SCREEN IDENTIFIES MULTIPLE GENES THAT INTERACT WITHDROSOPHILARAP/FZR AND SUGGESTS NOVEL CELLULAR ROLES

Abstract: In the developing Drosophila eye, Rap/Fzr plays a critical role in neural patterning by regulating the timely exit of precursor cells. Rap/Fzr (Retina aberrant in pattern/Fizzy related) is an activator of the E3 Ubiquitin ligase, the APC (Anaphase Promoting Complex-cyclosome) that facilitates the stage specific proteolytic destruction of mitotic regulators, such as cyclins and cyclin-dependent kinases. To identify novel functional roles of Rap/Fzr, we conducted an F(1) genetic modifier screen to identify genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 133 publications
1
12
0
Order By: Relevance
“…We also tested genetic interactions with the cell-cycle regulator, cyclin A ( cycA ). In alignment with a previous report (Kaplow et al., 2007), fzrRNAi1 partially rescued the strong eye size reduction of ey > cycARNAi (Figure S2M), whereas cdc16RNAi1 did not affect the phenotype (Figure S2N). These results strongly suggest that the differentiation failure phenotype induced by ey>cdc16RNAi1 is separable from cell-cycle defects.…”
Section: Resultssupporting
confidence: 93%
“…We also tested genetic interactions with the cell-cycle regulator, cyclin A ( cycA ). In alignment with a previous report (Kaplow et al., 2007), fzrRNAi1 partially rescued the strong eye size reduction of ey > cycARNAi (Figure S2M), whereas cdc16RNAi1 did not affect the phenotype (Figure S2N). These results strongly suggest that the differentiation failure phenotype induced by ey>cdc16RNAi1 is separable from cell-cycle defects.…”
Section: Resultssupporting
confidence: 93%
“…Rap/Fzr genetically interacts with Loco, a positive effector of glia differentiation: Our genetic modifier studies identified Loco as a dominant suppressor of the rap/fzr rough-eye phenotype (Kaplow et al 2007). Loco plays a critical role in embryonic asymmetric cell division of neuroblasts during gliogenesis and also mediates septate junction formation during glia differentiation (Schwabe et al 2005;Yu et al 2005).…”
Section: Resultsmentioning
confidence: 99%
“…The interaction between Rap/Fzr and cellular substrates requires either a KEN box or a Destruction box motif (D box: RXXLXXXN) (Pfleger and Kirschner 2000). Bioinformatic analyses of Loco amino acid sequence showed both a KEN box and a Destruction box, raising the possibility that Loco is a potential substrate of Rap/Fzr (Kaplow et al 2007). To test whether Rap/Fzr and Loco physically interact in vivo, we performed a series of co-immunoprecipitation experiments with larval brain lysates from UAS-loco-GFP; repo-GAL4.…”
Section: Resultsmentioning
confidence: 99%
“…As genetic screens can identify genes that interact through nontranscriptional mechanisms (Kaplow et al 2007;Cao et al 2008;Kim et al 2010), and given that we detected minimal changes in gene expression at the transcriptional level, we elected to perform a rough eye enhancer genetic screen on a panel of RNAi lines. We observed that overexpression of HDAC4 in the eye with the glass multimer reporter driver (GMR-GAL4) (Freeman 1996) results in a rough eye phenotype, with disorganized ommatidia and bristles ( Figure 1A) compared to the GMR-GAL4 control ( Figure 1B).…”
Section: Identification Of Hdac4 Gene Targets In Neuronsmentioning
confidence: 99%
“…Analysis of differential expression confirmed that HDAC4 was significantly overexpressed by approximately twofold, but we did not observe global changes in gene expression. Thirteen genes (excluding HDAC4 and white, which was the selectable marker for transgenesis) were increased in abundance and 13 were decreased ( A screen for modifiers of the HDAC4-induced rough eye phenotypeAs genetic screens can identify genes that interact through nontranscriptional mechanisms (Kaplow et al 2007;Cao et al 2008;Kim et al 2010), and given that we detected minimal changes in gene expression at the transcriptional level, we elected to perform a rough eye enhancer genetic screen on a panel of RNAi lines. We observed that overexpression of HDAC4 in the eye with the glass multimer reporter driver (GMR-GAL4) (Freeman 1996) results in a rough eye phenotype, with disorganized ommatidia and bristles ( Figure 1A) compared to the GMR-GAL4 control ( Figure 1B).…”
mentioning
confidence: 99%